The 'moral panics' behind television advertising regulations in Malaysia - Mokhtar, Aida (IIUM Press, 2011)
A country that is a mélange of diverse ethnic groups would detest the nuances of panic what more of moral panic and this is the case with Malaysia. The friction happening in 1969 that amounted to deaths and injury has led to the promotion on national unity between people whose culture and race are remarkably different and the disproportionate economic backgrounds that the Malays and Chinese encouraged the government to come with a solution for promoting the idea of an equal footing in the economic ownership between the races. Of focus in this chapter is the role of the media and television advertising in bringing the different races together in Malaysia.